Helicobacter pylori serology using specimens collected on filter paper. - Huang, Z (1991)
A simple method for the collection of blood specimens on filter paper for serology of Helicobacter pylori was devised. Blood was freshly applied to small Whatman 3 mm filter paper and allowed to dry. Serological activity, as measured by reactivity to H pylori antigens (AMRAD, Australia), was retained after storage for one month at both room temperature and at 4 degrees C. This technique eliminates formal venepuncture, separation of sera, and arduous packaging of specimens to be sent to the laboratory.